The Development of Virtual Classroom Spaces: A Bibliometric Review of A Decade of Scopus Research - Muflihatul Laela Sari; Viky Nur Vambudi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the development of virtual classroom studies through mapping trends in scientific publications, author contributions, institutional affiliations, productive countries, documents with the highest citations, and the development of research themes based on Scopus indexed literature. This study uses a bibliometric method by utilizing publication data from English-language journal articles indexed by Scopus and analyzed using bibliometric mapping tools to identify research development patterns. The results of the study show that publications related to virtual classrooms have increased and reached the peak of development in 2023. The United States is the country with the highest publication contribution, the University of Florida is the most prolific affiliate, and Huang Y is listed as the author with the highest number of publications. The theme analysis shows that virtual reality, human, education, and student are the main themes in virtual classroom research, while the COVID-19 pandemic is one of the issues that drives the development of the study. This study concludes that virtual classrooms are developing as a strategic field of study in digital education transformation, with advanced research opportunities on the integration of immersive technology and pedagogical innovation.